Bioekologi Nyamuk Armigeres, Mansonia, Aedes, Anopheles dan Coquilletidia (Diptera: Culicidae) di Kecamatan Jebus Kabupaten Bangka Barat - Sarlinda Sari; Eddy Nurtjahya; Awit Suwito (Department of Biology, Faculty of Agriculture, Fisheries and Biology, University of Bangka Belitung, 2022)
Bangka Belitung is one of the provinces in Indonesia that is endemic to the disease transmitted exclusively by mosquitoes, such as filariasis, dengue hemorrhagic fever (DHF) and malaria. Limitations of information on risk factors of filariasis and dengue hemorrhagic fever (DHF), mosquito bioecology, and the endemic environment, it has not obtained specific and efficient ways in disease control. This research aims to reveal biodiversity and mosquito bioecology in Jebus District, West Bangka Regency. This research is an explorative one. Collections of adult mosquitoes mostly obtained Armigeres subalbatus (59 individuals). Totally 115 individuals of mosquitoes collected in Jebus District were 115 individuals consisting of genera Armigeres (Ar. subalbatus, Ar. malayi, and Ar. moultoni), Mansonia (Ma. dives and Ma. annulata), Aedes (Ae. aegypti, Ae. albopictus and Aedes sp.), Coquillettidia (Coquillettidia ochracea) and Anopheles (An. letifer). Collecting of larvae stage obtained two species of mosquitoes i.e. Aedes aegypti and Aedes albopictus, which were found in the water / drum shelter, bathtub, used bottles and the ex-tin mined pond.